Tethered lunar subsatellites for multipoint and low altitude measurements. (November 2016) - Collier, Michael R.; Vondrak, Richard R.; Hoyt, Robert P.; Mesarch, Michael A.; Farrell, William M.; Keller, John W.; Clark, Pamela E.; Petro, Noah E.; Hwang, Kyoung-Joo
Abstract: The difficulty in making global measurements in orbit close to planetary bodies (and in particular the Moon) seriously constrains our ability to collect crucial, high-resolution data. We describe a unique and groundbreaking approach using tethered subsatellites to make measurements arbitrarily close to planetary surfaces, particularly those with no atmosphere, and to determine altitude profiles of geophysical parameters. The approach is feasible with current technology, and the subsatellite could be as small as a CubeSat. The initial results of a feasibility study and mission design for a tethered lunar CubeSat indicate that it is achievable. Highlights: Groundbreaking use of tethered subsatellites to make measurements close to planetary surfaces. Approach is feasible with current technology. Subsatellite could be as small as a CubeSat.